Business Process Management Workshops BPM 2015, 13th International Workshops, Innsbruck, Austria, August 31 - September 3, 2015, Revised Papers - Reichert, Manfred; Reijers, Hajo A. (Lecture Notes in Business Information Processing,, 2016)
This book constitutes the refereed proceedings of ten international workshops held in Innsbruck, Austria, in conjunction with the 13th International Conference on Business Process Management, BPM 2015, in September 2015. The seven workshops comprised Adaptive Case Management and other Non-workflow Approaches to BPM (AdaptiveCM 2015), Business Process Intelligence (BPI 2015), Social and Human Aspects of Business Process Management (BPMS2 2015), Data- and Artifact-centric BPM (DAB 2015), Decision Mining and Modeling for Business Processes (DeMiMoP 2015), Process Engineering (IWPE 2015), and Theory and Applications of Process Visualization (TaProViz 2015). The 42 revised papers presented were carefully reviewed and selected from 104 submissions. In addition, four short papers and one keynote (from TAProViz) are also included in this book.